Crystallization behavior of poly(lactic acid) with a self-assembly aryl amide nucleating agent probed by real-time infrared spectroscopy and X-ray diffraction. (December 2017) - Zhang, Huanhuan; Wang, Songjie; Zhang, Shaoyuan; Ma, Ruixue; Wang, Yaming; Cao, Wei; Liu, Chuntai; Shen, Changyu
Abstract: The effect of a self-assembly nucleating agent, N, N ′, N ″-tricyclohexyl-1, 3, 5-benzenetricarboxylamide (BTCA), on the crystallization behavior of poly(lactic acid) (PLA) was probed by time-resolved Fourier transform infrared spectroscopy (FTIR) and wide angle X-ray diffraction (WAXD). The vibrational changes associated with inter- and intra-chain interactions during crystallization were monitored. In the initial period of crystallization, the order of intensity changes is as follows: 1458 cm −1 > 1210 cm −1 » 921 cm −1, 1458 cm −1 ∼ 1210 cm −1 > 921 cm −1, and 1458 cm −1 ∼ 1210 cm −1 ∼ 921 cm −1 for neat PLA, PLAs containing 0.1 wt% and 0.3 wt% BTCA, respectively. This indicates that BTCA can accelerate both the formation of skeletal conformational-ordered structure and, especially, the 103 helix one. The incorporation of BTCA changes the crystallization mechanism but has no impact on the crystal form of PLA.